The impact of globalization on the sustainable development of enterprises – the case of Bulgaria, Croatia and Romania - Misztal, Anna; Kowalska, Magdalena (Wpływ globalizacji na zrównoważony rozwój przedsiębiorstw – przypadek Bułgarii, Chorwacji i Rumunii, 2020)
The main aim of this paper is to assess the impact of globalization on the sustainable development of enterprises in Bulgaria, Croatia, and Romania. Globalization and sustainable development are popular and commonly used terms. They relate to contemporary conditions of business development and their progress is inevitable. The sustainable development of enterprises can be defined as the development taking place in three spheres of economic, social and environmental protection. Globalization concerns the processes of the integration and interdependence of economies, enterprises and institutions. The first part of this paper shows selected theoretical issues related to the impact of globalization on sustainable business development. The second, main part, presents the results of the study, which show that globalization has a statistically significant, positive impact on the sustainable development of enterprises in Bulgaria, Croatia and Romania in the period from 2008 to 2019
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 3, s. 42-56
Keywords: globalization; sustainable development of enterprises; globalizacja; zrównoważony rozwój przedsiębiorstwa